2016
DOI: 10.2134/cftm2015.0164
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence and Market Assurance for Production of Non–Genetically Engineered Alfalfa Hay and Forage in a Biotech Era

Abstract: The introduction of genetically engineered (GE) alfalfa requires a mechanism for producers to successfully grow and market alfalfa (Medicago sativa L.) hay destined for GE-sensitive markets such as organic and export. A process of coexistence includes elements of respect for diverse agricultural systems, improved communication, scientific knowledge, and market clarity. A definition for "non-GE alfalfa forage" is proposed, along with suggested production protocols. These protocols include securing non-GE-detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…In 2013, nearly 22% of total respondents reported growing either genetically engineered hay (19%) or seed (3%). This is in line with adoption rates of 30% in 2014, as reported by Putnam et al (2016). We found that the number of seed producers who reported growing genetically engineered seed in 2013 did not differ by study area and ranged from 11 to 17%; across the three study areas; the majority of seed producers were producing conventional seed (Table 2).…”
Section: Overview Of Respondentssupporting
confidence: 87%
See 1 more Smart Citation
“…In 2013, nearly 22% of total respondents reported growing either genetically engineered hay (19%) or seed (3%). This is in line with adoption rates of 30% in 2014, as reported by Putnam et al (2016). We found that the number of seed producers who reported growing genetically engineered seed in 2013 did not differ by study area and ranged from 11 to 17%; across the three study areas; the majority of seed producers were producing conventional seed (Table 2).…”
Section: Overview Of Respondentssupporting
confidence: 87%
“…The presence of different market classes and the need to support consumer preferences and farmer choice has brought the concept of agricultural coexistence to the forefront. For this paper we adopt the coexistence definition put forward by Putnam et al (2016): “Successful coexistence” is “the ability of diverse systems (GE [genetically engineered], organic, non‐GE) to thrive without undue influence of neighbors or resorting to extraordinary protection measures.”…”
Section: Useful Conversionsmentioning
confidence: 99%
“…The issues of the cost of real-time PCR based systems, which are the standard reference method for transgene detection, when used for routine field-based applications have been addressed in grain crops already through efficient sampling strategies [27][28][29] and through the development of other diagnostic tools such as semi-quantitative enzyme-linked immunosorbent assay (ELISA) (e.g., [29]) which have also been used to detect the presence of the CP4 EPSPS gene in GM bentgrass [30] and alfalfa [10], and through the use of plasmid DNA for the calibrated detection of specific transgenic events (e.g., [31,32]. More recently novel DNA amplification techniques such as recombinase polymerase amplification (RPA) for the rapid point-of-use screening of transgenic soybean seeds [33] have been developed.…”
Section: Detection Of Transgenes In Forages and Related Agricultural mentioning
confidence: 99%
“…Along with these general guidelines a number of specific interventions have been proposed to facilitate the co-existence of GM and non-GM alfalfa hay crops [9,10]. These are also applicable to perennial forages grown for dairy grazing and include,…”
Section: Management Practices That Could Be Used To Further Minimise mentioning
confidence: 99%
See 1 more Smart Citation